A new approach for the copper-catalyzed functionalization of alkyl hydroperoxides with organosilicon compounds via in-situ-generated alkylsilyl peroxides. (23rd April 2022) - Zhong, Wenfeng; Xu, Weiping; Yang, Qin; Kato, Terumasa; Liu, Yan; Maruoka, Keiji
Abstract: Using organosilicon compounds of the type Me3 SiX (X = CN, N3, Cn F2n+1, and halogens) and an amine base, alkylsilyl peroxides were generated in situ from the corresponding alkyl hydroperoxides. Subsequent in situ copper-catalyzed homolytic cleavage of the alkylsilyl peroxides afforded alkyl radicals, which were then trapped with a nucleophile X (X = CN, N3, Cn F2n+1, and halogens) to furnish coupling products with new carbon–carbon, carbon–nitrogen, or carbon–halogen bonds in good to high yields. In addition, 1-(trimethylsilyl)morpholine can also be employed for the in-situ-generation of alkylsilyl peroxides, which are subsequently utilized for N-alkylation of amides, arylations, and borylations with high efficiency. Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Image 1